(untitled) (Fiep Bulletin - online, 2020)
With the increase in the number of academies in Campina Grande - PB, the increase in the number of dietary supplements available on the market and looking for a perfect body on behalf of users of the academies, aroused the interest of the study on the consumption of supplements by the their customers. With the emergence of new dietary supplements on the market today, the use by customers has increased greatly, as proof of his lack of results from manufacturers, that even before the launch would have to be done research proving its effectiveness, with lack of adequate information by end users - so called by the manufacturers - the client often does the intake of certain supplements without even knowing what they are taking or what they are taking, since most do not have accompanying a sports nutritionist and go for the head of one or the other. Most customers do not have the proper nutritional information and make the intake higher than indicated supplements for your body, it ends up causing inefficiency in the product or even problems in your health. Thus, the aim of this study is to test the use of supplements by clients academies in Campina Grande - PB and pass information so that they can have a little more knowledge not doing the indiscriminate use of supplements, going looking for a professional in the area for a job can be done safely. The study objective was successfully achieved since completed their goals, but they need more studies to affirm on this subject